Effectiveness of delivering disability competencies to undergraduate medical students in a foundation course in a Government Medical College: A quasi-experimental study - Deepthi R; Shivakumar Ajay Kumar; Anuradha Shenoy; Suthanthira Kannan (Zanjan University of Medical Sciences and Health Services, 2024)
Background & Objective: Globally, 16% of the world's population, or 1 in 6 of us, experience significant disability. Persons with Disabilities (PWDs) are likely to encounter insufficient healthcare provider skills to address their specific needs, to encounter denial of care, and to experience mistreatment from healthcare providers. In the diverse field of medicine, medical practitioners are often confronted with the challenge of providing equitable and effective healthcare to all patients, including those with disabilities. Material & Methods: A quasi experimental study to evaluate the effectiveness of a need-based structured module on disability competencies with a pre-, post-, and retention post-test design. The study included 75 first year MBBS foundations students who completed the entire module. Data on knowledge regarding disability competencies was collected using a pre-test, an immediate post-test, and a retention post-test after 3 months of intervention. We used RMANOVA to compare the pretest, post-test, and 3-month retention post test scores at the 0.05 significance level. Results: Totally, 45 (53.3%) boys and 35 (46.7%) girls participated in the study. Overall pretest scores was 10.92 ± 1.75 (95% CI: 10.54 - 11.30), which significantly increased to 19.24 ± 2.63 (95% CI: 18.66-19.82) (p < 0.001) following the course, and the scores were sustained at 18.67 ± 2.72 (95% CI: 18.07-19.27) even after 3 months following training. RMANOVA determined the increase in mean scores was statistically significant between assessment stages (pretest, post-test, and retention test) (F (1.3, 95.5) = 460.69, p < 0.001). The scores increased significantly across all domains of disability competency training (p < 0.001). A paired t test between scores shows a significant increase in scores across all domains between pre-test and post-test (p < 0.001); scores did not reduce significantly even after 3 months. Conclusion: Training medical students in disability competencies using structured modules increased their knowledge significantly post-training, which was retained even after 3 months. Disability competency training is crucial to ensure equitable and inclusive healthcare, reduce healthcare disparities, and improve overall patient care outcomes.